Sobre la enseñanza propia comunitaria. El caso de Aragón - Fernández Clemente, Eloy (Studia Historica. Historia Contemporánea, 2010)
RESUMEN: Al reflexionar, desde su propia experiencia de historiador y profesor de Historia Económica, sobre las circunstancias que rodean la tan discutida enseñanza de la Historia propia («nacional» o «regional»), de cada Comunidad Autónoma española y, en concreto la suya, de Aragón, el autor se propone contribuir al debate sobre su obligatoriedad, sentido, finalidad, razonabilidad. Quiere ser una propuesta abierta y poco dogmática, un ensayo con diversas consideraciones que van desde la política y la ideología a la didáctica, y que aporta la experiencia concreta del Instituto de Ciencias de la Educación de la Universidad de Zaragoza, que lleva realizando una preparación muy sólida con vistas a las próximas transferencias de las enseñanzas primaria y media, que de seguro contemplarán la de la Historia de Aragón como un pilar de formación de esos estudiantes. Palabras clave: Historia nacional. Historia regional, Historiografía, Identidad colectiva. Didáctica de la historia. ABSTRACT: Upon reflecting, from his own experience as a historian and professor of Economic History, on the circumstances surrounding the much-debated teaching of the particular History ('national' or 'regional') of each Autonomous Community of Spain, and specifically of Aragón, the author aims to contribute to this debate on its necessity, sense, purpose and reasonableness. It aspires to be a proposal that is open and not very dogmatic, an essay with various considerations that go from politics and ideology to didactics, and which contributes the particular experience of the Institute of Educational Sciences (Instituto de Ciencias de la Educación) oí the University of Zaragoza, which has been Ediciones Universidad de Salamanca Stud, hist., H.^ cont., 13-14, pp. 29-37 carrying out solid preparation with a view to the forthcoming transfer of primary and middle education, which will surely contemplate that of the History of Aragón as a mainstay of the education of these students. Thus it will be necessary for primary and secondary school teachers to be wellprepared in a subject that cannot be improvised. This explains why it is urgent for this problem to be raised at the university level, which is where these future teachers are being trained. Key words: National History, Regional History, Historiography, Collective Identity, Didactics of History.